Performance and carcass quality of feedlot- or pasture-finished Nellore heifers according to feeding managements in the postweaning phase - Casagrande, Daniel Rume; Azenha, Mariana Vieira [UNESP]; Vieira, Bruno Ramalho [UNESP]; Resende, Flavio Dutra de; Faria, Marcelo Henrique de; Berchielli, Telma Teresinha [UNESP]; Ruggieri, Ana Claudia [UNESP]; Reis, Ricardo Andrade [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2013)
The objective of this study was to evaluate the postweaning history of heifers kept on marandu grass pastures with three canopy heights, in a continuous-grazing system, during the rainy period, on feedlot-or pasture finishing. The effects of three canopy heights (15, 25 and 35 cm) associated with two supplements (mineral salt and protein-energy supplement) and two finishing systems in the dry period (feedlot and open pasture) were studied in the postweaning period during the rainy season. The adopted design was completely randomized, with seven replications (animals) in a 2 x 2 factorial arrangement. The animals which received protein-energy supplement reached the finishing period with greater body weight in relation to those fed mineral salt. In both feedlot and pasture finishing systems, compensatory gain effect was observed in the animals that remained on the low pastures during postweaning compared with the high pastures. This compensatory gain was not verified in the animals that received protein-energy supplement in relation to the mineral salt, and thus the animals were slaughtered beforehand. The heifers on pastures with 25 or 35 cm in height were slaughtered in the same period, and those kept on the low pastures were slaughtered afterwards. The studied factors in the postweaning phase did not affect the carcass characteristics. Animals finished in feedlot slaughtered with the same body weight as those finished on pasture show greater carcass yield, subcutaneous fat deposition and renal pelvic and inguinal fat and greater losses with trimmings for cleaning the main hindquarter meat cuts; however, they provide cuts with the same weight but greater fat cover.
Keywords: animal performance; Animal supplementation; canopy height; Intake; Meat cuts